The paradox of networked politics: A critical examination of presidential campaigns in the United States - Stromer-Galley, Jennifer (AoIR Selected Papers of Internet Research, 2013)
Although new scholarship has heralded the digital affordances of social media on the Internet to transform political activism in the United States, the same transformation has not occurred in presidential campaigns. Campaign practices in the United States have used social media to harness citizens in the service of winning the election, not in better empowering and engaging citizens in the political process. Thus, although political elections are essential to a democracy, political campaigns are decidedly undemocratic.